Role of Genetic Variability, Heritability and Genetic Advance for Various Traits of Bread Wheat (Triticum aestivum L.) under Variable Sowing Times - Tolwani, Sonal; Shukla, R. S. (International Journal of Bio-resource and Stress Management, 2022)
The field experiments were conducted with 54 genotypes including 10 lines, 4 testers and 40 F1’s. The pure seeds of these 14 selected genotypes were grown in crossing blocks to obtain 40 cross combinations, during November–March of rabi 2016–17. These lines and testers along with obtained 40 crosses (F1’s) were grown in randomised complete block design with 3 replications in 3 sowing dates during November–March in rabi 2017-18 and observations were recorded. Each genotype was sown with spacing of 20 cm between rows and 10 cm between plants. Data recorded for 21 characters including different morphological, physiological and quality traits from 5 randomly selected plants of each replication and mean data used for analysis. In the current investigation, value of PCV is higher than GCV for all the 21 characters. The high values of PCV and GCV were observed for GYPP, BYPP, SV, NEPP, and NTPP in E1, GYPP, BYPP, NEPP, NTPP, HI and SV in E2 and GYPP, BYPP, PL, NTPP, and NEPP in E3. However, we noticed maximum PCV and GCV for GYPP followed by BYPP in E1, E2, and E3. Even though remaining traits showed moderate or low PCV and GCV. High heritability, along with high genetic advance were recorded for the traits GYPP, WG, SV, BYPP, 1000 GW, CC, HI, PL, NEPP, and NTPP. Overall, our findings of various variability parameters may help in the selection of high yielding genotypes under different sowing times in wheat crop.